Editorial (Latin-American Journal of Computing, 2020)
Dear readers,Welcome to Number 2 Volume 7 of Latin-American Computing Journal. This is the second issue that we make available during the global COVID-19 pandemic and with it the 2020 activity closes. On this occasion, the editors of LAJC wish to thank the many hours of dedication in the fulfillment of their professional, academic and research responsibilities of our readers and collaborators during this time.In this regular issue, I am pleased to present an interesting variety of relevant research articles in their respective fields. We hope that the eight selected topics will generate interest and encourage our readers in their various activities. A brief synopsis of each is shown below.The article "Digital agriculture in pitahaya crop" presents a technological solution that provides relevant information for precision agriculture. This solution was implemented in the Palora region, Morona Santiago Province, Ecuador where there are 1,528 hectares of pitahaya crops. In the article "Anomaly detection under a cognitive security model", an architecture is implemented to differentiate the behavior of benign from malicious network traffic, to support the cognitive processes of security analysts. In the third article "Design and implementation of a wireless sensor network with LoRa technology for industrial monitoring", an architecture for short-range communications with low-cost equipment is proposed. This solution was validated in two industrial scenarios. The study “A comparative evaluation of the performance of open-source SDN controllers" creates a software-defined network using lightweight virtualization mechanisms to compare latency, performance, and scalability of three open protocol controllers. The authors of “An implementation of a virus focused on mobile devices with Android. An Ethical Hacking Event” use a virtualized platform to perform penetration tests on Android systems to study the vulnerabilities of said systems. The article "Digital image processing in the creation of an intelligent system prototype for text detection and recognition in the labeling process of electrical cable" uses a database of images of cables of different color, text color, cable type and caliber, similar to those used in industrial plants, obtaining average error rates of 6.54%, 3.97% and 2.53%. The following article “Rain gauge data logger based on ATMEL microcontroller and LoRa transceiver” implements a weather station with low power consumption and reduced costs for data acquisition, storage, and transmission. During the confinement, the authors of the article "Use of technology in Industry 4.0 to support the fight against the COVID-19 epidemic through a hand hygiene dispenser using locally built devices" used easily available and low cost materials to manufacture a device that detects the presence of the user's hands in front of the sanitizing liquid dispenser duct.I thank the authors and reviewers of this issue for their valuable and generous contribution. Finally, a well-deserved annual recognition to all the authors and reviewers who have selflessly supported LAJC since its inception in 2014.Enjoy reading this issue!